The Impact of a Family-Centred Intervention for Parents of Children with Developmental Disabilities: A Model Project in Rural Ireland - Roy McConkey; Pauline O'Hagan; Joanne Corcoran (MDPI AG, 2023)
The greater risk of poor mental health and social isolation, experienced by parents of children with developmental disabilities, is compounded by family circumstances and living in rural settings. Often parents receive little personal support. Family-centred interventions have been recommended internationally for promoting children's development, as well as boosting parental wellbeing. Yet, in many countries, current service provision is predominately child-focused and clinic-centred. An innovative, family-centred support service was designed and evaluated in a rural county of Ireland. Support staff visit the family home every month for around one year with regular check-ins by phone. The service aims included setting developmental goals for the child that were agreed with parents, alongside actions to address the personal needs of parents and siblings. In addition, community activities are identified or created to promote the social inclusion of the child and family in local communities, as well as locating opportunities for social activities for mothers. To date, 96 families with 110 children have been involved and three monthly reviews have been undertaken of each child's progress. Baseline measures on parents' mental health and social isolation were gathered and repeated when parents had completed their involvement with the project, along with qualitative information regarding the parents' experiences. Most children attained their learning targets, alongside those selected as personal goals by parents; in particular, parents reported their child's greater involvement in community activities, increased knowledge and skills, and with more confidence and resilience. Significant increases in parental well-being scores were reported, but there was a limited impact on their social participation and that of their child. This evidence-based model of provision is an example of how current social care provision for families who have a child with developmental disabilities could be cost-effectively re-envisioned even in rural areas.